Preparation method of high-end medical and hygienic superfine denier hot-melt self-adhesive fiber
Modified polyethylene terephthalate by argon plasma treatment and combined with the addition of hybrid fillers of single-layer graphene oxide and chitosan, the problem of insufficient antibacterial and antibacterial properties of existing ES fibers in the medical field is solved, and high-end medical and health ultrafine denier hot melt self-adhesive fibers with excellent mechanical properties and antibacterial effects are prepared.
Patent Information
- Application Number
- CN202411571232.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing ES fibers have insufficient antibacterial properties and stability in the medical field, making it difficult to meet the needs of high-end medical and health products.
The modified polyethylene terephthalate was treated with argon plasma as the core layer, and the hybrid filler of a single layer of graphene oxide and N-trimethoxysilpropylethylenediamine triac acid aqueous solution was added, combined with the amino reaction of chitosan, and a cortical material with excellent mechanical properties and antibacterial effects was prepared.
It improves the antibacterial and mechanical properties of ES fibers, enhances the thermal stability and antistatic effects of fibers, and meets the high standard needs of high-end medical and health products.
Smart Images

Figure BDA0005120506570000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of sanitary fibers, in particular to a method for preparing high-end medical and sanitary ultrafine denier hot-melt self-adhesive fibers. Background Art
[0002] The "ES" in ES fiber is the abbreviation of "Ethylene-Propylene Side By Side", which means it is a two-component structure. The core layer is usually polypropylene, which plays the main supporting role, and the skin layer is polyethylene, which plays the role of hot melt bonding. During the heat treatment process, the fibers of this fiber can be bonded to each other to form a non-woven fabric without adhesive. Hot air non-woven fabrics made of ES fiber are fluffy, soft, high-strength, good permeability and adsorption capacity, and are often used in the fields of sanitary materials, thermal insulation filling materials and filter materials.
[0003] In addition, ES fiber also shows good application prospects in the fields of automobiles, textiles, construction, etc. The high-end development of downstream industries in the future will also promote the growth of ES fiber market demand. As the application fields of ES fiber gradually expand, the market demand for ES fiber will continue to be released. In the future, my country's ES fiber industry has broad room for improvement and good market development prospects. Because ES fiber is a clean fiber that does not use adhesives, it has been widely used in the covering of sanitary products and medical surgical supplies. Although the existing ES fiber has reached the quality standards for sanitary products and medical surgery, and has great advantages in safety, heat resistance, durability, and mechanical properties, as a medical product, the antibacterial and antibacterial properties and stability of ES fiber still need to be improved. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing high-end medical and sanitary ultrafine denier hot-melt self-adhesive fibers to solve the problems existing in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing high-end medical and health ultra-fine denier hot-melt self-adhesive fiber, comprising the following preparation steps:
[0006] (1) The modification source is argon gas, and the processing power of the plasma generator is 50-300 W; the treatment time of the plasma acting on the surface of the polyethylene terephthalate is 0.5-10 min, and the vacuum degree is 5-20 Pa, thereby obtaining pretreated polyethylene terephthalate;
[0007] (2) Mixing a monolayer graphene oxide with ethanol at a mass ratio of 1:500 and dispersing it by ultrasonic treatment for 2 hours; then adding an aqueous solution of N-trimethoxysilylpropylethylenediaminetriacid with a mass of 1-5 times that of the monolayer graphene oxide, and stirring at 40-60°C for 12 hours; after the reaction is completed, adding methanol at a volume ratio of 1:1 to the reaction solution, transferring to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washing with acetone, ethanol and deionized water in turn, and drying at room temperature for 6 hours to obtain a hybrid filler; adding 50 parts of pretreated polyethylene terephthalate into a high-speed mixer, mixing at a speed of 250-350 rpm for 5-10 minutes, heating to 200-250°C, adding 5-12 parts of hybrid filler, operating at a speed of 600-900 rpm, and mixing for 20 minutes to obtain a core layer material;
[0008] (3) Dissolving 10-20 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid in 63 parts of N,N-dimethylformamide and 30-40 parts of an initiator in 200 parts of an interfacial agent respectively, adding the two solutions to a reaction device containing 80-140 parts of low-density polyethylene and 40-50 parts of an auxiliary grafting monomer styrene under an inert gas atmosphere, reacting at 100° C. for 30 minutes, cooling to room temperature, filtering, and then extracting with methanol and acetone respectively, and vacuum drying at 0.085 MPa for 4 hours to obtain modified polyethylene; adding 30-40 parts of the modified polyethylene to a high-speed mixer, mixing at a speed of 250-350 rpm for 5-10 minutes, heating to 140-180° C., adding 2-7 parts of chitosan, operating at a speed of 600-900 rpm, and mixing for 20 minutes to obtain a skin material;
[0009] (4) feeding the skin layer material and the core layer material separately; the skin layer material is 150-180°C, the core layer material is 220-250°C, and after melting for 30 minutes, the material is extruded in filament form by a screw extruder; the skin layer wraps the core layer, and the mass ratio of the skin layer to the core layer is 3:2, and composite spinning is performed to form composite fibers; the extruded raw fibers are wound together, and because the production frequency of the post-spinning is inconsistent with the production frequency of the front-spinning, the products of the front-spinning stage are collected and dropped into barrels in this step, and then transferred to the post-spinning production line; and then secondary drawing is performed: the primary drawing is performed between the first drawing machine and the second drawing machine, and the secondary drawing is performed between the first drawing machine and the second drawing machine. The first-stage drawing is carried out in the steam box between the second and third drawing machines; the tows coming out of the third drawing machine enter the wire stacking machine for stacking; the stacked tows enter the three-roller amplitude modulation frame of the crimping machine, and then enter the crimping machine; the crimped short fibers are evenly laid on the chain plate of the relaxation and heat setting machine under the action of the laying machine, and are subjected to high-temperature relaxation and setting and forced air cooling, and the short tows are dried, set and cooled; the wire strips after relaxation and heat setting enter the cutting machine, and the wire strips are cut into high-end medical and health ultra-fine denier hot-melt self-adhesive fibers of different lengths; then they are graded, packaged and put into storage according to product requirements.
[0010] Furthermore, in step (1), the argon gas flow rate is 20-40 mL / min.
[0011] Furthermore, the preparation method of the monolayer graphene oxide in the step (2) is as follows: 1 part of graphite, 2 parts of potassium permanganate and 2 parts of manganese dioxide are added to 30 parts of 98wt% concentrated sulfuric acid, reacted at -10°C for 48h, and then diluted to 10 times the volume with deionized water; the residual strong oxidant is removed with hydrogen peroxide, and the obtained product is repeatedly centrifuged and washed with water for 5 times, with the centrifuge speed being 5000rpm, until the liquid pH reaches 5-7, thereby obtaining a monolayer graphene oxide.
[0012] Furthermore, in step (2), the ultrasonic power is 40 kHz.
[0013] Furthermore, in step (2), the mass concentration of the N-trimethoxysilylpropylethylenediaminetriacid aqueous solution is 10 wt%.
[0014] Furthermore, in step (3), the initiator is dibenzoyl peroxide.
[0015] Furthermore, in the step (3), the inert gas is nitrogen.
[0016] Furthermore, in step (3), the interfacial agent is xylene.
[0017] Furthermore, in step (4), the spinning speed is 2200 m / min, the temperature of screw zone 1 is controlled at 220°C, the temperature of screw zone 2 is controlled at 260°C, the temperature of screw zone 3 is controlled at 290°C, the temperature of screw zone 4 is controlled at 280°C, the temperature of screw zone 5 is controlled at 290°C, and the diameter of the spinneret hole is 1.6 mm.
[0018] Furthermore, the high-end medical and sanitary ultrafine denier hot-melt self-adhesive fiber is 0.5 dtex.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention uses hybrid filler-modified polyethylene terephthalate as the core layer and chitosan-added low-density polyethylene as the skin layer to prepare high-end medical and health ultrafine denier hot-melt self-adhesive fiber to achieve the effects of antibacterial and excellent mechanical properties.
[0021] Firstly, oxygen-containing functional groups are introduced into the polyethylene terephthalate core material by argon plasma treatment, and the core material is modified without affecting the performance of the core material and in a safe and non-toxic manner, so that the core material is rich in hydroxyl groups, carboxyl groups and the like; the hydroxyl groups on the surface of a single-layer graphene oxide are grafted with ethylenediaminetetraacetic acid through silanization and added into the cortex as a hybrid filler for modification; while the hybridization process solves the problem of easy agglomeration of graphene oxide, the silanization covalent bond connection makes the prepared ES fiber stable in performance and improves the thermal stability of the core layer during high-temperature melt spinning, thereby achieving excellent mechanical properties; the single-layer graphene oxide is dispersed in the core material, and its sharp edge can destroy the cell wall of bacteria to achieve a sterilization effect, and also optimizes the mechanical properties of the core layer;
[0022] Secondly, low-density polyethylene is grafted with unsaturated carboxylic acid monomers to synthesize new copolymer-modified polyethylene; the modified polyethylene and the amino group of chitosan undergo Michael addition reaction to generate Schiff base, so as to prepare a safe and antibacterial cortex; the hydroxyl group on the chitosan can also react and combine with the carboxyl group of the hybrid filler in the core layer, so that the combination of the core layer and the cortex is more stable, and the overall mechanical properties of the ES fiber are improved; on this basis, the raw materials and modified materials and the preparation process used in the present invention are safe and non-toxic, and non-metallic substances are used as effective antibacterial factors, which not only meet the antibacterial requirements of medical and health care, but also reduce the generation of static electricity, so that the prepared ES fiber has a good antistatic effect; and in the textile processing of ultrafine denier fibers, the same yarn count correspondingly increases the number of fiber cross-sections in the yarn, thereby greatly improving the uniformity and strength of the yarn, and is conducive to increasing the yarn count. DETAILED DESCRIPTION
[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0024] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the high-end medical and health ultra-fine denier hot-melt self-adhesive fibers prepared in the following examples are as follows:
[0025] Antibacterial property: Escherichia coli and were selected as representatives of Gram-negative bacteria, and Staphylococcus aureus was selected as a representative of Gram-positive bacteria; according to the provisions of "GB / T20944.3-2088 Evaluation of antibacterial properties of textiles", the antibacterial rates of the examples and comparative examples against Escherichia coli and Staphylococcus aureus were tested; according to the provisions of "GB / T20944.2-2007 Evaluation of antibacterial properties of textiles Part 2 Absorption method", the antibacterial rates of the samples prepared in the examples and comparative examples against fungi were tested.
[0026] Mechanical properties: According to GB / T14337-2008 Test method for tensile properties of chemical staple fibers, the breaking strength and breaking elongation of the samples prepared in the examples and comparative examples were tested.
[0027] Example 1; (1) The modification source is argon gas, the flow rate is 20 mL / min, and the processing power of the plasma generator is 50 W; the treatment time of the plasma acting on the surface of polyethylene terephthalate is 0.5 min, the vacuum degree is 5 Pa, and the pretreated polyethylene terephthalate is obtained;
[0028] (2) adding 1 part of graphite and 2 parts of potassium permanganate and 2 parts of manganese dioxide, a strong oxidant, to 30 parts of concentrated sulfuric acid with a concentration of 98 wt%, reacting at -10°C for 48 hours, and then diluting to 10 times the volume with deionized water; removing the residual strong oxidant with hydrogen peroxide, and repeatedly centrifuging and washing the obtained product with water for 5 times at a centrifuge speed of 5000 rpm until the liquid pH reaches 5, thereby obtaining a monolayer of graphene oxide; mixing a monolayer of graphene oxide with ethanol at a mass ratio of 1:500, and dispersing it by ultrasonic treatment for 2 hours at an ultrasonic power of 40 kHz; then adding 1 times the mass of the monolayer of graphene oxide The N-trimethoxysilylpropylethylenediamine triacid aqueous solution was added and stirred at 40°C for 12 hours; after the reaction was completed, methanol was added in a volume ratio of 1:1 to the reaction solution, and the mixture was transferred to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washed with acetone, ethanol and deionized water in turn, and dried at room temperature for 6 hours to obtain a hybrid filler; 50 parts of pretreated polyethylene terephthalate were added to a high-speed mixer, mixed at a speed of 250rpm for 5 minutes, heated to 200°C, and then 5 parts of hybrid fillers were added, and the mixture was operated at a speed of 600rpm and mixed for 20 minutes to obtain a core layer material;
[0029] (3) Dissolving 10 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid in 63 parts of N,N-dimethylformamide and 30 parts of initiator dibenzoyl peroxide in 200 parts of interface agent xylene respectively, adding the two solutions to a reaction device containing 80 parts of low-density polyethylene and 40 parts of auxiliary grafting monomer styrene under a nitrogen atmosphere, reacting at 100° C. for 30 minutes, cooling to room temperature, filtering, and then extracting with methanol and acetone respectively, and vacuum drying at 0.085 MPa for 4 hours to obtain modified polyethylene; adding 30 parts of modified polyethylene to a high-speed mixer, mixing at a speed of 250 rpm for 5 minutes, heating to 140° C., adding 2 parts of chitosan, operating at a speed of 600 rpm, and mixing for 20 minutes to obtain a skin material;
[0030] (4) feeding the skin layer material and the core layer material separately; the skin layer material is 150°C, the core layer material is 220°C, and after melting for 30 minutes, the material is extruded in filament form by a screw extruder; the skin layer wraps the core layer, the mass ratio of the skin layer to the core layer is 3:2, and the composite fiber is formed by composite spinning at a spinning speed of 2200m / min, the temperature of the first zone of the screw is controlled at 220°C, the temperature of the second zone of the screw is controlled at 260°C, the temperature of the third zone of the screw is controlled at 290°C, the temperature of the fourth zone of the screw is controlled at 280°C, the temperature of the fifth zone of the screw is controlled at 290°C, the diameter of the spinneret hole is 1.6mm, and an ultrafine denier fiber of 0.5dtex is prepared; the extruded raw silk is wound together, and because the production frequency of the post-spinning is inconsistent with the production frequency of the pre-spinning, this step will be the pre-spinning stage The products of the first stage are collected and dropped into barrels, and then transferred to the post-spinning production line; then the secondary drafting is carried out: the first-stage drafting is carried out between the first drafting machine and the second drafting machine, and the secondary drafting is carried out in the steam box between the second drafting machine and the third drafting machine; the tow coming out of the third drafting machine enters the stacking machine for stacking; the stacked tow enters the three-roller amplitude modulation frame of the crimping machine, and then enters the crimping machine; the crimped short fibers are evenly laid on the chain plate of the relaxation and heat setting machine under the action of the laying machine, and are subjected to high-temperature relaxation and setting and forced air cooling, and the short tows are dried, set and cooled; the silk strips after relaxation and heat setting enter the cutting machine, and the silk strips are cut into high-end medical and health ultra-fine denier hot-melt self-adhesive fibers of different lengths; then according to product requirements, they are graded, packaged and put into storage.
[0031] Example 2; (1) The modification source is argon gas, the flow rate is 30 mL / min, and the processing power of the plasma generator is 175 W; the treatment time of the plasma acting on the polyethylene terephthalate surface is 5 min, the vacuum degree is 12 Pa, and the pretreated polyethylene terephthalate is obtained;
[0032] (2) adding 1 part of graphite and 2 parts of potassium permanganate and 2 parts of manganese dioxide, a strong oxidant, to 30 parts of concentrated sulfuric acid with a concentration of 98 wt%, reacting at -10°C for 48 hours, and then diluting to 10 times the volume with deionized water; removing the residual strong oxidant with hydrogen peroxide, and repeatedly centrifuging and washing the obtained product with water for 5 times at a centrifuge speed of 5000 rpm until the liquid pH reaches 6, thereby obtaining a single-layer graphene oxide; mixing a single-layer graphene oxide with ethanol at a mass ratio of 1:500, and dispersing it by ultrasonic treatment for 2 hours at an ultrasonic power of 40 kHz; then adding 3 times the mass of the single-layer graphene oxide N-trimethoxysilylpropylethylenediamine triacid aqueous solution, and stirred at 50°C for 12 hours; after the reaction is completed, methanol is added in a volume ratio of 1:1 to the reaction solution, and the mixture is transferred to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washed with acetone, ethanol and deionized water in sequence, and dried at room temperature for 6 hours to obtain a hybrid filler; 50 parts of pretreated polyethylene terephthalate are added to a high-speed mixer, mixed at a speed of 300 rpm for 7.5 minutes, heated to 225°C, and then 8.5 parts of hybrid filler are added, and the mixture is operated at a speed of 750 rpm and mixed for 20 minutes to obtain a core layer material;
[0033] (3) Dissolve 15 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid in 63 parts of N,N-dimethylformamide and 35 parts of initiator dibenzoyl peroxide in 200 parts of interface agent xylene, add the two solutions to a reaction device containing 105 parts of low-density polyethylene and 45 parts of auxiliary grafting monomer styrene under a nitrogen atmosphere, react at 100° C. for 30 minutes, cool to room temperature, filter, extract with methanol and acetone respectively, and vacuum dry at 0.085 MPa for 4 hours to obtain modified polyethylene; add 35 parts of modified polyethylene into a high-speed mixer, mix at a speed of 300 rpm for 7.5 minutes, heat to 160° C., add 4.5 parts of chitosan, operate at a speed of 750 rpm, and mix for 20 minutes to obtain a skin material;
[0034] (4) feeding the skin layer material and the core layer material separately; the skin layer material is at 165°C, the core layer material is at 235°C, and after melting for 30 minutes, the material is extruded in filament form by a screw extruder; the skin layer wraps the core layer, the mass ratio of the skin layer to the core layer is 3:2, and the composite fiber is formed by composite spinning at a spinning speed of 2200 m / min, the temperature of the first zone of the screw is controlled at 220°C, the temperature of the second zone of the screw is controlled at 260°C, the temperature of the third zone of the screw is controlled at 290°C, the temperature of the fourth zone of the screw is controlled at 280°C, the temperature of the fifth zone of the screw is controlled at 290°C, the diameter of the spinneret hole is 1.6 mm, and an ultrafine denier fiber of 0.5 dtex is prepared; the extruded raw silk is wound together, and because the production frequency of the post-spinning is inconsistent with the production frequency of the pre-spinning, this step will be the pre-spinning stage The products of the first stage are collected and dropped into barrels, and then transferred to the post-spinning production line; then the secondary drafting is carried out: the first-stage drafting is carried out between the first drafting machine and the second drafting machine, and the secondary drafting is carried out in the steam box between the second drafting machine and the third drafting machine; the tow coming out of the third drafting machine enters the stacking machine for stacking; the stacked tow enters the three-roller amplitude modulation frame of the crimping machine, and then enters the crimping machine; the crimped short fibers are evenly laid on the chain plate of the relaxation and heat setting machine under the action of the laying machine, and are subjected to high-temperature relaxation and setting and forced air cooling, and the short tows are dried, set and cooled; the silk strips after relaxation and heat setting enter the cutting machine, and the silk strips are cut into high-end medical and health ultra-fine denier hot-melt self-adhesive fibers of different lengths; then according to product requirements, they are graded, packaged and put into storage.
[0035] Example 3; (1) The modification source is argon gas, the flow rate is 40 mL / min, and the processing power of the plasma generator is 300 W; the plasma treatment time on the polyethylene terephthalate surface is 10 min, the vacuum degree is 20 Pa, and the pretreated polyethylene terephthalate is obtained;
[0036] (2) adding 1 part of graphite and 2 parts of potassium permanganate and 2 parts of manganese dioxide, a strong oxidant, to 30 parts of concentrated sulfuric acid with a concentration of 98 wt%, reacting at -10°C for 48 hours, and then diluting to 10 times the volume with deionized water; removing the residual strong oxidant with hydrogen peroxide, and repeatedly centrifuging and washing the obtained product with water for 5 times at a centrifuge speed of 5000 rpm until the liquid pH reaches 7, thereby obtaining a single-layer graphene oxide; mixing a single-layer graphene oxide with ethanol at a mass ratio of 1:500, and dispersing it by ultrasonic treatment for 2 hours at an ultrasonic power of 40 kHz; then adding 5 times the mass of the single-layer graphene oxide N-trimethoxysilylpropylethylenediamine triacid aqueous solution was added and stirred at 60°C for 12 hours; after the reaction was completed, methanol was added in a volume ratio of 1:1 to the reaction solution, and the mixture was transferred to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washed with acetone, ethanol and deionized water in sequence, and dried at room temperature for 6 hours to obtain a hybrid filler; 50 parts of pretreated polyethylene terephthalate were added to a high-speed mixer, mixed at a speed of 350rpm for 10 minutes, heated to 250°C, and then 12 parts of hybrid fillers were added, and the mixture was operated at a speed of 900rpm and mixed for 20 minutes to obtain a core layer material;
[0037] (3) Dissolve 20 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid in 63 parts of N,N-dimethylformamide and 40 parts of initiator dibenzoyl peroxide in 200 parts of interface agent xylene, add the two solutions to a reaction device containing 140 parts of low-density polyethylene and 50 parts of auxiliary grafting monomer styrene under a nitrogen atmosphere, react at 100° C. for 30 minutes, cool to room temperature, filter, extract with methanol and acetone respectively, and vacuum dry at 0.085 MPa for 4 hours to obtain modified polyethylene; add 40 parts of modified polyethylene into a high-speed mixer, mix at a speed of 350 rpm for 10 minutes, heat to 180° C., add 7 parts of chitosan, operate at a speed of 900 rpm, and mix for 20 minutes to obtain a skin material;
[0038] (4) feeding the skin layer material and the core layer material separately; the skin layer material is 180°C, the core layer material is 250°C, and after melting for 30 minutes, the material is extruded in filament form by a screw extruder; the skin layer wraps the core layer, the mass ratio of the skin layer to the core layer is 3:2, and the composite fiber is formed by composite spinning at a spinning speed of 2200m / min, the temperature of the first zone of the screw is controlled at 220°C, the temperature of the second zone of the screw is controlled at 260°C, the temperature of the third zone of the screw is controlled at 290°C, the temperature of the fourth zone of the screw is controlled at 280°C, the temperature of the fifth zone of the screw is controlled at 290°C, the diameter of the spinneret hole is 1.6mm, and an ultrafine denier fiber of 0.5dtex is prepared; the extruded raw silk is wound together, and because the production frequency of the post-spinning is inconsistent with the production frequency of the pre-spinning, this step will be the pre-spinning stage The products of the first stage are collected and dropped into barrels, and then transferred to the post-spinning production line; then the secondary drafting is carried out: the first-stage drafting is carried out between the first drafting machine and the second drafting machine, and the secondary drafting is carried out in the steam box between the second drafting machine and the third drafting machine; the tow coming out of the third drafting machine enters the stacking machine for stacking; the stacked tow enters the three-roller amplitude modulation frame of the crimping machine, and then enters the crimping machine; the crimped short fibers are evenly laid on the chain plate of the relaxation and heat setting machine under the action of the laying machine, and are subjected to high-temperature relaxation and setting and forced air cooling, and the short tows are dried, set and cooled; the silk strips after relaxation and heat setting enter the cutting machine, and the silk strips are cut into high-end medical and health ultra-fine denier hot-melt self-adhesive fibers of different lengths; then according to product requirements, they are graded, packaged and put into storage.
[0039] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that there is no step (1), and step (2) is changed to: 1 part of graphite, 2 parts of potassium permanganate, a strong oxidant, and 2 parts of manganese dioxide are added to 30 parts of concentrated sulfuric acid with a concentration of 98wt%, reacted at -10°C for 48h, and then diluted to 10 times the volume with deionized water; the residual strong oxidant is removed with hydrogen peroxide, and the obtained product is repeatedly centrifuged and washed with water for 5 times, with the centrifuge speed of 5000rpm, until the liquid pH reaches 6, to obtain a monolayer graphene oxide; a monolayer graphene oxide with a mass ratio of 1:500 is mixed with ethanol, and dispersed for 2h by ultrasonic treatment, with an ultrasonic power of 40kHz; then added A N-trimethoxysilylpropylethylenediamine triacid aqueous solution with a mass of 3 times that of a single-layer graphene oxide is added, and stirred at 50°C for 12 hours; after the reaction is completed, methanol is added in a volume ratio of 1:1 to the reaction solution, and the mixture is transferred to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washed with acetone, ethanol and deionized water in sequence, and dried at room temperature for 6 hours to obtain a hybrid filler; 50 parts of polyethylene terephthalate are added to a high-speed mixer, mixed at a speed of 300 rpm for 7.5 minutes, heated to 225°C, and then 8.5 parts of hybrid filler are added, and the mixture is operated at a speed of 750 rpm and mixed for 20 minutes to obtain a core layer material; the remaining steps are the same as in Example 2.
[0040] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (2) is different. Step (2) is changed to: add 1 part of graphite and 2 parts of strong oxidant potassium permanganate and 2 parts of manganese dioxide to 30 parts of concentrated sulfuric acid with a concentration of 98wt%, react at -10°C for 48h, and then dilute to 10 times the volume with deionized water; remove the residual strong oxidant with hydrogen peroxide, and repeatedly centrifuge and wash the obtained product with water for 5 times at a centrifuge speed of 5000rpm until the liquid pH reaches 6, thereby obtaining a single-layer graphene oxide; add 50 parts of pretreated polyethylene terephthalate into a high-speed mixer, mix at a speed of 300rpm for 7.5min, heat to 225°C, add 8.5 parts of single-layer graphene oxide, operate at a speed of 750rpm, and mix for 20min to obtain a core layer material; the remaining steps are the same as Example 2.
[0041] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different, and step (3) is changed to: graphene and ethanol in a mass ratio of 1:500 are mixed and dispersed by ultrasonic treatment for 2 hours, and the ultrasonic power is 40kHz; then an aqueous solution of N-trimethoxysilylpropylethylenediaminetriacid with a mass of 3 times that of the monolayer graphene oxide is added, and stirred at 50°C for 12 hours; after the reaction is completed, methanol is added in a volume ratio of 1:1 to the reaction solution, and the mixture is transferred to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washed with acetone, ethanol and deionized water in turn, and dried at room temperature for 6 hours to obtain a hybrid filler; 50 parts of pretreated polyethylene terephthalate are added to a high-speed mixer, mixed at a speed of 300 rpm for 7.5 minutes, heated to 225°C, 8.5 parts of hybrid filler are added, and the mixture is operated at a speed of 750 rpm and mixed for 20 minutes to obtain a core layer material; the remaining steps are the same as Example 2.
[0042] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (3) is different. Step (3) is changed to: add 35 parts of low-density polyethylene into a high-speed mixer, mix at a speed of 300 rpm for 7.5 minutes, heat to 160°C, add 4.5 parts of chitosan, operate at a speed of 750 rpm, mix for 20 minutes, and obtain a skin material; the remaining steps are the same as Example 2.
[0043] Comparative Example 5; The difference between Comparative Example 5 and Example 2 lies in the difference in step (3), whereby step (3) is modified as follows: 15 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid are dissolved in 63 parts of N,N-dimethylformamide and 35 parts of initiator dibenzoyl peroxide are dissolved in 200 parts of interface agent xylene, and the two solutions are added to a reaction device containing 105 parts of low-density polyethylene and 45 parts of auxiliary grafting monomer styrene under a nitrogen atmosphere, reacted at 100°C for 30 minutes, cooled to room temperature, filtered, extracted with methanol and acetone respectively, and vacuum dried at 0.085 MPa for 4 hours to obtain modified polyethylene as a skin material; the remaining steps are the same as those of Example 2.
[0044] Effect example
[0045] Table 1 below shows the performance analysis results of high-end medical and sanitary ultrafine denier hot-melt self-adhesive fibers using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.
[0046] Table 1
[0047]
[0048] From the comparison of the experimental data of mechanical properties of the embodiment and the comparative example, it can be found that the present invention first introduces oxygen-containing functional groups into the polyethylene terephthalate core layer raw material by argon plasma treatment, and performs modification without affecting the core material performance and in a safe and non-toxic manner, so that the core material is rich in hydroxyl, carboxyl and other groups; the surface hydroxyl groups of the monolayer graphene oxide are grafted with ethylenediaminetetraacetic acid through silanization as a hybrid filler and added into the skin layer for modification; the hybrid process solves the problem of easy agglomeration of graphene oxide, and the silanization covalent bond connection makes the prepared ES fiber performance stable, and improves the thermal stability of the core layer during high-temperature melt spinning; the monolayer graphene oxide is dispersed in the core material to optimize the mechanical properties of the core layer. Secondly, the polyethylene modified by grafting unsaturated carboxylic acid monomers with low-density polyethylene to synthesize a new copolymer is then added with chitosan, and the hydroxyl groups on the chitosan can react and combine with the carboxyl groups of the hybrid filler in the core layer, so that the combination of the core layer and the skin layer is more stable, and the overall mechanical properties of the ES fiber are improved. From the comparison of the experimental data of the antibacterial property of the embodiment and the comparative example, it can be found that the single-layer graphene oxide added by the present invention is dispersed in the core material, and its sharp edge can destroy the cell wall of bacteria to achieve the effect of sterilization. The modified polyethylene and the amino group of chitosan undergo Michael addition reaction to generate Schiff base, and a safe and antibacterial cortex is prepared, which synergizes with graphene to achieve the purpose of high-efficiency antibacterial. On this basis, the raw materials and modified materials and preparation process used in the present invention are safe and non-toxic, and non-metallic substances are used as antibacterial effective factors, which not only meet the antibacterial requirements of medical and health, but also reduce the generation of static electricity, so that the prepared ES fiber has a good antistatic effect; and in the textile processing of ultrafine denier fibers, the same yarn count will increase the number of fiber cross-sections in the yarn accordingly, thereby greatly improving the uniformity and strength of the yarn, and is conducive to increasing the yarn count.
[0049] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.
Claims
1. A method for preparing high-end medical and health ultra-fine denier hot-melt self-adhesive fiber, characterized in that: The method comprises the following preparation steps: (1) The modification source is argon gas, and the processing power of the plasma generator is 50-300 W; the treatment time of the plasma acting on the surface of the polyethylene terephthalate is 0.5-10 min, and the vacuum degree is 5-20 Pa, thereby obtaining pretreated polyethylene terephthalate; (2) Mixing a monolayer graphene oxide with ethanol at a mass ratio of 1:500 and dispersing it by ultrasonic treatment for 2 hours; then adding an aqueous solution of N-trimethoxysilylpropylethylenediaminetriacid with a mass of 1-5 times that of the monolayer graphene oxide, and stirring at 40-60°C for 12 hours; after the reaction is completed, adding methanol at a volume ratio of 1:1 to the reaction solution, transferring to a hydrothermal reactor for hydrothermal reaction at 160°C for 12 hours, and finally washing with acetone, ethanol and deionized water in turn, and drying at room temperature for 6 hours to obtain a hybrid filler; adding 50 parts of pretreated polyethylene terephthalate into a high-speed mixer, mixing at a speed of 250-350 rpm for 5-10 minutes, heating to 200-250°C, adding 5-12 parts of hybrid filler, operating at a speed of 600-900 rpm, and mixing for 20 minutes to obtain a core layer material; (3) Dissolving 10-20 parts by weight of 1-methacryloylpyrrolidine-2-carboxylic acid in 63 parts of N,N-dimethylformamide and 30-40 parts of an initiator in 200 parts of an interfacial agent respectively, adding the two solutions to a reaction device containing 80-140 parts of low-density polyethylene and 40-50 parts of an auxiliary grafting monomer styrene under an inert gas atmosphere, reacting at 100° C. for 30 minutes, cooling to room temperature, filtering, and then extracting with methanol and acetone respectively, and vacuum drying at 0.085 MPa for 4 hours to obtain a modified polyethylene; Add 30-40 parts of modified polyethylene into a high-speed mixer, mix at a speed of 250-350 rpm for 5-10 minutes, heat to 140-180°C, add 2-7 parts of chitosan, operate at a speed of 600-900 rpm, mix for 20 minutes, and obtain a skin material; (4) feeding the skin layer material and the core layer material separately; the skin layer material is 150-180°C, the core layer material is 220-250°C, and after melting for 30 minutes, the material is extruded in filament form by a screw extruder; the skin layer wraps the core layer, and the mass ratio of the skin layer to the core layer is 3:2, and composite spinning is performed to form composite fibers; the extruded raw fibers are wound together, and because the production frequency of the post-spinning is inconsistent with the production frequency of the front-spinning, the products of the front-spinning stage are collected and dropped into barrels in this step, and then transferred to the post-spinning production line; and then secondary drawing is performed: the primary drawing is performed between the first drawing machine and the second drawing machine, and the secondary drawing is performed between the first drawing machine and the second drawing machine. The first-stage drawing is carried out in the steam box between the second and third drawing machines; the tows coming out of the third drawing machine enter the wire stacking machine for stacking; the stacked tows enter the three-roller amplitude modulation frame of the crimping machine, and then enter the crimping machine; the crimped short fibers are evenly laid on the chain plate of the relaxation and heat setting machine under the action of the laying machine, and are subjected to high-temperature relaxation and setting and forced air cooling, and the short tows are dried, set and cooled; the wire strips after relaxation and heat setting enter the cutting machine, and the wire strips are cut into high-end medical and health ultra-fine denier hot-melt self-adhesive fibers of different lengths; then they are graded, packaged and put into storage according to product requirements.
2. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The argon gas flow rate in step (1) is 20-40 mL / min.
3. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The preparation method of the monolayer graphene oxide in the step (2) is as follows: 1 part of graphite, 2 parts of potassium permanganate and 2 parts of manganese dioxide, a strong oxidant, are added to 30 parts of concentrated sulfuric acid with a concentration of 98 wt%, reacted at -10°C for 48 hours, and then diluted to 10 times the volume with deionized water; the residual strong oxidant is removed with hydrogen peroxide, and the obtained product is repeatedly centrifuged and washed with water for 5 times at a centrifuge speed of 5000 rpm until the liquid pH reaches 5-7, thereby obtaining a monolayer graphene oxide.
4. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The ultrasonic power in the step (2) is 40 kHz.
5. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The mass concentration of the N-trimethoxysilylpropylethylenediaminetriacid aqueous solution in step (2) is 10 wt %.
6. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The initiator in step (3) is dibenzoyl peroxide.
7. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The inert gas in step (3) is nitrogen.
8. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: In the step (3), the interfacial agent is xylene.
9. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: In the step (4), the spinning speed is 2200 m / min, the temperature of the first zone of the screw is controlled at 220° C., the temperature of the second zone of the screw is controlled at 260° C., the temperature of the third zone of the screw is controlled at 290° C., the temperature of the fourth zone of the screw is controlled at 280° C., the temperature of the fifth zone of the screw is controlled at 290° C., and the diameter of the spinneret hole is 1.6 mm.
10. The method for preparing high-end medical and health ultrafine denier hot-melt self-adhesive fiber according to claim 1, characterized in that: The high-end medical and sanitary ultra-fine denier hot-melt self-adhesive fiber is 0.5 dtex.